AMBANG WAKTU PENDEDAHAN TELUR Lymnaea sp UNTUK MENGAMATI ABNORMALITAS EMBRIO SEBAGAI PARAMETER DALAM UJI HAYATI TERHADAP KARBAMAT - Hari Soepriandono; Bambang Irawan; Sri Puji Astuti Wahyuningsih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2000)
The aim of this study was to know the specific expose period of the Lymnaea sp.’s embyos and their age in order to utilization eggs of Lymnaea sp. in bioassay. Fifty individuals of Lymnaea sp. collected from Gonggan River Magetan were captured in laboratory. Egg cluster of each individual then was placed in petry dish which was filled by Baycarb 500 EC of 0.0001, 0.001 and 0.01 ppm. The result showed that 12 hours exposure in Baycarb 500 EC was the effective time since within 6 hours all of embryos were death and abnormalities of the survivals was detected in the embryos of 48 and 72 hours.